COVID‐19 associated with severe autoimmune hemolytic anemia. Issue 2 (16th December 2020) - Jacobs, Jeremy; Eichbaum, Quentin
Abstract: Background: Autoimmune hemolytic anemia (AIHA) has many known disease associations, including autoimmune, lymphoproliferative, and certain infectious diseases, as well as various medications. Studies have found that severe cases of coronavirus disease 2019 (COVID‐19) may be associated with coagulopathies; however, the potential association with AIHA is not clear. Case Report: A patient with no known risk factors or underlying predisposition for developing AIHA presented to a hospital with vague symptoms and profound anemia with a complicated blood bank evaluation. She was found to have COVID‐19 and AIHA, for which extensive laboratory testing was performed, including direct antiglobulin tests, elution studies, and cold agglutinin titers, to identify the causative autoantibody. She required multiple blood transfusions and therapeutic interventions before clinical stabilization. Discussion: AIHA is a complex disease with a spectrum of presentations and clinical severity. Many diseases have been associated with a propensity for developing AIHA; however, there are few cases in the literature of patients with COVID‐19 and AIHA. Most of the reports involve patients with other underlying conditions that are known to be associated with the development of AIHA. The presentation, clinical findings, and therapeutic interventions in a patient with severe AIHA, without other underlying conditions, in the setting of COVID‐19 are discussed. Conclusions: There are few reports of patients with concurrent COVID‐19 and AIHA, and the association is not clear. Although COVID‐19 has been shown to be associated with coagulopathies, more research is required to determine whether AIHA may also be a potential complication.